Influence of papain in biofilm formed by methicillin-resistant Staphylococcus epidermidis and methicillin-resistant Staphylococcus haemolyticus isolates (Brazilian Journal of Pharmaceutical Sciences, 2014)
Methicillin-resistant Staphylococcus epidermidis (MRSE) and methicillin-resistant Staphylococcus haemolyticus (MRSHa) are important coagulase-negative staphylococci. They are often isolated from bacteremia in humans mainly due to their ability to form biofilm on the surfaces of medical devices. Papain is a complex mixture of proteolytic enzymes and peroxidases extracted from the latex of Carica papaya and it is recognized by accelerating the healing process of wounds. This study aimed to evaluate the ability of the MRSE and MRSHa isolates to produce biofilms. Besides this, the ability of papain to inhibit the formation of biofilms or to disrupt the ones already formed by those bacteria was analyzed. Thirty MRSHa and 30 MRSE were isolated from bacteremia and used in this study. It was observed that papain has ability to reduce biofilms formed by MRSE (p < 0.06) and by MRSHa (p = 0.0005). In addition, papain was able to disrupt mature biofilms made by MRSE (p = 0.014). No antibacterial activity of papain was observed for any isolates of MRSE and MRSHa tested. Papain has been demonstrated as a potential product for reducing biofilm.